2019
DOI: 10.1002/asi.24228
|View full text |Cite
|
Sign up to set email alerts
|

Bias effects, synergistic effects, and information contingency effects: Developing and testing an extended information adoption model in social Q&A

Abstract: To advance the theoretical understanding on information adoption, this study tries to extend the information adoption model (IAM) in three ways. First, this study considers the relationship between source credibility and argument quality and the relationship between herding factors and information usefulness (i.e., bias effects). Second, this study proposes the interaction effects of source credibility and argument quality and the interaction effects of herding factors and information usefulness (i.e., synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…In this approach, the obtained data is used for analysing the relationship among the path coefficients to minimize residual variance or error terms of the endogenous variables (Ahmadian & Abdolmaleki, 2018;Hair et al, 2014). According to (Sun et al ,2019), PLS-SEM modelling estimates the theoretical model involved in the research through Smart PLS 3.1.2. For current research, the PLS-SEM was chosen as a statistical technique to analyse the data.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, the obtained data is used for analysing the relationship among the path coefficients to minimize residual variance or error terms of the endogenous variables (Ahmadian & Abdolmaleki, 2018;Hair et al, 2014). According to (Sun et al ,2019), PLS-SEM modelling estimates the theoretical model involved in the research through Smart PLS 3.1.2. For current research, the PLS-SEM was chosen as a statistical technique to analyse the data.…”
Section: Resultsmentioning
confidence: 99%
“…As predicted, we confirmed that all three types of dependency relations had significant effects on users' attachment to the social Q&A community. For example, the social Q&A community allows users to spend time to search information, read and ask what they want to know (Liu and Jansen, 2017; Sun et al , 2019). Moreover, users continue to stay in the social media because of the goals of understanding, orientation, and play (Chiu and Huang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Zhihu community, functioning as a social Q&A community, is one of the most popular online communities in China with more than 100 million registered members. The target social Q&A community owns a huge number of users and content creators, which has constituted a valuable data source for academic studies (Sun et al , 2019). We invited participants by adding the link to the online questionnaire through several online channels, such as the instant message tools (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations